2020
DOI: 10.1121/10.0000617
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of fin whale 20 Hz call detections by deep-water mobile autonomous and stationary recorders

Abstract: Acoustically equipped deep-water mobile autonomous platforms can be used to survey for marine mammals over intermediate spatiotemporal scales. Direct comparisons to fixed recorders are necessary to evaluate these tools as passive acoustic monitoring platforms. One glider and two drifting deep-water floats were simultaneously deployed within a deep-water cabled hydrophone array to quantitatively assess their survey capabilities. The glider was able to follow a pre-defined track while float movement was somewhat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 79 publications
1
22
0
Order By: Relevance
“…The models performed the best for fin whales, predicting their presence with an 88% precision at both sites. This is similar performance to that reported for fin whale detectors in other studies (e.g., Buchan et al, 2019;Fregosi et al, 2020). The model also performed well for NARW at the slope site (15% false discovery rate) and humpback whales at the shelf site (21% false discovery rate).…”
Section: Discussionsupporting
confidence: 86%
“…The models performed the best for fin whales, predicting their presence with an 88% precision at both sites. This is similar performance to that reported for fin whale detectors in other studies (e.g., Buchan et al, 2019;Fregosi et al, 2020). The model also performed well for NARW at the slope site (15% false discovery rate) and humpback whales at the shelf site (21% false discovery rate).…”
Section: Discussionsupporting
confidence: 86%
“…Underwater gliders are similar to deep-water profiling floats in their operation and communication, but have the added advantage of being able to traverse currents (Rudnick et al, 2004). However, this horizontal movement comes at the cost of increased lowfrequency (<100 Hz) noise from water flow and noise from platform operation which could mask cetacean sounds of interest (Fregosi et al, 2020). Further, the continual movement (both horizontally and vertically) means that local sound propagation conditions and therefore the detection radius around a mobile platform may be continually changing (Helble et al, 2013;Gkikopoulou, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Acoustically equipped mobile autonomous platforms, such as underwater gliders and profiling floats, can effectively record a variety of marine mammal species (Baumgartner et al, 2013;Matsumoto et al, 2013;Nieukirk et al, 2016;Küsel et al, 2017) including beaked whales (Klinck et al, 2012), delphinids (Silva et al, 2019), and minke whales (Klinck et al, 2015). Detection rates of the low-frequency fin whale (Balaenoptera physalus) 20-Hz pulse have been quantitatively compared to a cabled bottom-mounted hydrophone array (Fregosi et al, 2020). However, no quantitative comparison has been made of detection capabilities for these platforms relative to other well-characterized bottom-moored systems, such as the Highfrequency Acoustic Recording Package (HARP; Wiggins and Hildebrand, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…A better option would be to position the hydrophone on a tether, or possibly use a winch system to deploy an array of hydrophones some distance from the vehicle's hull, while the electronics would remain inside and thermally controlled. A recent study of flow noise on ocean gliders demonstrated that lower vehicle speeds (<25 cm s -1 ) result in lower ambient noise levels in the 50-200 Hz band, to the point where ambient noise levels were comparable to fixed acoustic recorders (Fregosi et al, 2020). In contrast, increased vehicle speeds will increase flow noise energy.…”
Section: Inclusion Of Pam Systems On Ocean World Exploration Vehiclesmentioning
confidence: 99%